Low Dispersion Performance of Plastic Fiber Grating Using Genetic Algorithms - Hisham, Hisham K. (Al-Nahrain Journal for Engineering Sciences, 2018)
In this paper, we suppose a method for reducing the dispersion in the plastic optical fiber (POF) Bragg gratings based on optimizing the grating coupling-strength (?) using genetic algorithms. The effects of average refractive index (?n) and temperature (T) change on the dispersion properties are investigated numerically. It is found that the amplitude of the ?n for low dispersion performance needs to be reduced at the cost of the design complexity of the POF Bragg gratings. Owing to the unusually large and negative thermo-optic coefficient of the POF, the dispersion due to the wavelength shift induced by the temperature variation will be reduced by operating at high ? value. Results showed that by optimizing the ? value a very large dispersion reduction range has been obtained, from 1178 to 11.5 ps/nm at 30 mm grating length.